Surgical Management of Over-gestation in a Female Dog: A Case Report - Dutt, Ravi; Anil; Garbhit; Bulbul; Kumar, Vinay; Niwas, Ram; Dalal, Jasmer; Singh, Gyan (Animal Reproduction Update, 2025)
A 2-year-old female dog was brought to VCC, LUVAS, with a history of overgestation  (68 days’ pregnancy). After a complete gynaeco-clinical examination, a caesarean  section was performed, and 5 foetuses including one mummified foetus were  delivered. The female dog recovered uneventfully following normal postoperative  management.
Keywords: Caesarean section; Female dog; mummified fetus; Overgestation; Top of Form